A rare case of acquired benign tracheoesophageal fistula. Issue 2 (15th February 2020) - Bouayyad, Sarah; Beena, Meera; Nigam, Ajay
Abstract: Acquired benign tracheoesophageal fistula (TOF) is a rare medical condition that usually results from trauma, foreign bodies or granulomatous infections. This is an unusual presentation of a male patient with a history of laryngectomy who has had over a period of several years inappropriately and vigorously used valve cleaning brushes to clean tracheal secretions, which has led to the formation of a TOF. Due to the patient's obsessive habit, we could not manage him using conventional surgical methods. Instead, we opted for the placement of a salivary bypass tube, which yielded good results and recovery. To the best of our knowledge, no other case of similar aetiology has been published. We would like to highlight the importance of appropriate patient selection and education prior to performing a tracheoesophageal puncture to avoid developing life-threatening complications as demonstrated in our case report.